Effects of thoracic squeezing on airway secretion removal in mechanically ventilated patients - Farkhondeh Yousefnia-Darzi; Farideh Hasavari; Tahereh Khaleghdoost; Ehsan Kazemnezhad-Leyli; Malahat Khalili (Wolters Kluwer Medknow Publications, 2016)
Background: Accumulation of secretions in the airways of patients with an endotracheal tube and mechanical ventilation will have serious consequences. One of the most common methods of airway clearance is endotracheal suctioning. In order to facilitate discharge of airway secretion resulting in promotion of gas exchange, chest physiotherapy techniques can be used at the time of expiration before suction. Materials and Methods: In this clinical trial with a cross-over design, 50 mechanically ventilated patients admitted to intensive care units (ICUs) were randomly divided into two groups of thoracic squeezing. In each patient, two interventions of endotracheal suctioning were conducted, one with and the other without thoracic squeezing during exhalation, with a 3 h gap between the two interventions and an elapse of three respiratory cycles between the number of compressions. Sputum secreted was collected in a container connected to a suction catheter and weighed. Data were recorded in data gathering forms and analyzed using descriptive and inferential statistics (Wilcoxon and independent t-test, Chi-square) in SPSS version 16. Results: Findings showed that the mean weight of the suction secretions removed from airway without thoracic squeezing was 1.35 g and that of suction secretions removed by thoracic squeezing was 1.94 g. Wilcoxon test showed a significant difference regarding the rate of secretion between the two techniques (P = 0.003). Conclusions: According to the study findings, endotracheal suction with thoracic squeezing on expiration helps airway secretion discharge more than suction alone in patients on mechanical ventilators and can be used as an effective method.